2016
DOI: 10.1016/j.algal.2016.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and classification of highly productive microalgae strains discovered for biofuel and bioproduct generation

Abstract: This paper describes the characteristics of microalgal strains that originated out of an 31 isolation and screening project included within the National Alliance for Advanced 32 Biofuels and Bioproducts (NAABB). The project's goal was to identify new potential 33 platform strains with high growth rates and/or lipid productivities. To classify the best 34 performing strains, we conducted a combined microscopic and phylogenetic analysis. 35Among the best performing strains were many coccoid green algae. Several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
0
10

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(62 citation statements)
references
References 81 publications
1
51
0
10
Order By: Relevance
“…This species is aerial to terrestrial with humidity (40 %) or without (Song & Singh 2014), and at high altitudes (Gopalakrishnan et al 2014). It shows distribution in different regions (Abe et al 2004, Tschaikner et al 2007, Tschaikner et al 2008, Uzonov et al 2008, Song & Singh 2014, and was recently reported in North America (Neofotis et al 2016). However prior to this study Coelastrella had not been reported in tropical regions of North America (Yucatan Peninsula).…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…This species is aerial to terrestrial with humidity (40 %) or without (Song & Singh 2014), and at high altitudes (Gopalakrishnan et al 2014). It shows distribution in different regions (Abe et al 2004, Tschaikner et al 2007, Tschaikner et al 2008, Uzonov et al 2008, Song & Singh 2014, and was recently reported in North America (Neofotis et al 2016). However prior to this study Coelastrella had not been reported in tropical regions of North America (Yucatan Peninsula).…”
Section: Discussionmentioning
confidence: 42%
“…It was recently reported for the first time in freshwater in North America (Neofotis et al 2016), but prior to this study it had not been reported in a tropical region of North America (Yucatan Peninsula). Its habitats range from aerial to terrestrial with relative humidity (40 %) or without (Song & Singh 2014), as well as at high altitudes (Gopalakrishnan et al 2014).…”
mentioning
confidence: 92%
“…Fluorescence-based methods such as fluorescence-activated cell sorting (FACS) are widely utilized to determine the characteristics of cells based on fluorescent staining of particular target molecules, such as intracellular lipids in microalgae [30,31]. Besides fluorescence, direct imaging of cells to determine their phenotypes and/or characteristics is also becoming increasingly popular thanks to the advances in imaging flow cytometry [32,33]. Although extremely powerful and versatile, several limitations exist [18].…”
Section: Dep Technology For Cell Population Analysismentioning
confidence: 99%
“…The advent of molecular methods permitted establishing a taxonomic framework, resulting in splitting the vast genus Chlorella into many monophyletic genera, providing a framework for the classification of strains of evolutionary, ecological or biotechnological interest (e.g. Bock et al, 2011;Krienitz et al, 2015;Neofotis et al, 2016).…”
Section: Introductionmentioning
confidence: 99%